The Relationship between the Environment and Diarrhea in Toddlers in Petonggan Village, Rakit Kulim District, Indragiri Hulu Regency in 2022: Hubungan Lingkungan Dengan Kejadian Diare Pada Balita Di Desa Petonggan Kecamatan Rakit Kulim Kabupaten Indragiri Hulu Tahun 2022 - Rita Rostandi; Jihan Natassa; Hayana Hayana (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Diarrhea is also called vomiting, a child under five is said to have diarrhea when he has a bowel movement that exceeds the usual daily limit, has loose stools, his stools soften until they are liquid. The purpose of this study was to determine the relationship between the environment and the incidence of diarrhea in children under five. Data obtained from Petonggan Village midwives found the incidence of diarrhea in toddlers in Petonggan Village in 2020 was 160 toddlers. This research is a quantitative research, with the type of cross-sectional research. The population in this study were all toddlers living in Petonggan Village, Rakit Kulim District, Indragiri Hulu Regency, amounting to 144 toddlers. A sample of 106 children under five, sampling using Proportional Random Sampling, namely by taking a sample to calculate the proportion based on the type of sub-population, and then a random sample is taken. Data analysis was univariate and bivariate with chi-square test. The results showed that there was a relationship between clean water sources and the incidence of diarrhea in children under five with a p value = 0.015 and a POR value = 3.136. There is a relationship between landfills and the incidence of diarrhea in toddlers with a p value = 0.027 and the POR value = 2.813. There is a relationship between sewerage and the incidence of diarrhea in children under five with p = 0.003 and POR = 3.769. There is a relationship between family latrine ownership and the incidence of diarrhea in children under five with p = 0.015 and POR = 3.241. There is a relationship between the behavior of washing hands with soap and the incidence of diarrhea in toddlers with a p value = 0.005 and a POR value = 3.600. It is hoped that the Petonggan Village Community Health Center will provide counseling to the community about the importance of environmental hygiene so that children are not susceptible to diarrhea.